2010
DOI: 10.2807/ese.15.48.19734-en
|View full text |Cite
|
Sign up to set email alerts
|

Control of a multi-hospital outbreak of KPC-producing Klebsiella pneumoniae type 2 in France, September to October 2009

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 14 publications
3
113
0
11
Order By: Relevance
“…Indeed, patient morbidity and mortality due to GI endoscopes contaminated with these antibiotic-resistant bacteria have been documented [13,[20][21][22]24,[26][27][28][29][30][31][32][33] . Reports of GI endoscopes transmitting other types of bacteria, too, as well as viruses and other infectious agents, also have been published during the past 30 years.…”
Section: Findings and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, patient morbidity and mortality due to GI endoscopes contaminated with these antibiotic-resistant bacteria have been documented [13,[20][21][22]24,[26][27][28][29][30][31][32][33] . Reports of GI endoscopes transmitting other types of bacteria, too, as well as viruses and other infectious agents, also have been published during the past 30 years.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…And, with the recent emergence of the "superbug" known as carbapenem-resistant Enterobacteriaceae, or "CRE", infection control in this setting has taken on even more urgency and closer examination [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Even if infection does ensue, it may not be immediately apparent after exposure to the endoscope because of silent transmission and colonization. [4][5][6] In 1 recent endoscopy-associated, multidrug-resistant organism (MDRO) outbreak, investigators found that several patients were asymptomatic carriers of an extended-spectrum b-lactamase-producing Klebsiella pneumoniae for more than 10 months after exposure to contaminated endoscopes. Others presented with symptomatic bloodstream infections or biliary tract infections.…”
Section: Reply To Petersenmentioning
confidence: 99%
“…1,2 Several recent publications, including the paper in this issue of ICHE by Wendorf et al, 3 have associated multidrug-resistant (MDR) bacterial infections, especially carbapenemase-resistant Enterobacteriaceae (CRE), in patients who have undergone ERCP with reprocessed duodenoscopes. [3][4][5] Unlike other endoscope-associated outbreaks, these recent outbreaks occurred even when the manufacturer's instructions and professional guidelines were followed correctly. 3,4 The purpose of this commentary is 3-fold: (1) to briefly discuss the outbreak described by Wendorf et al; (2) to discuss what alternatives exist today that might improve the safety margin associated with duodenoscope reprocessing; and (3) to discuss how to prevent future outbreaks associated with ERCP endoscopes and other gastrointestinal (GI) endoscopes.…”
mentioning
confidence: 99%
“…If endoscopes are found to be contaminated with potential pathogens (eg, enteric Gramnegative bacilli), the clinical impact of such contamination needs to be quantified. In addition, based on the studies by Wendorf et al and others, [3][4][5] it would be reasonable to consider periodic microbiologic surveillance of duodenoscopes to assess microbial contamination as one component of a prevention strategy. However, culture results are delayed 2-3 days, and many questions related to microbiologic surveillance remain: What cutoff should be used to define proper disinfection (eg, 0 pathogens or a higher number [eg, <10 CFU] of enteric pathogens per channel)?…”
mentioning
confidence: 99%